Characteristics of chromophoric dissolved organic matter in the Northern Andaman Sea - Ruoshi Zhao; Zhongqiao Li; Aung Aung Aye; Hao Zheng; Weifang Jin; Jingjing Zhang; Feng Zhou; Hongliang Li; Nang Mya Han; Myat Lwin; Jianfang Chen; Jianfang Chen (Frontiers in Marine Science, 2023)
The dissolved organic matter (DOM) in the ocean is a large carbon pool that plays an important role in the global carbon cycle. Investigation of the characteristics and behaviors of DOM in some areas facilitates a better understanding of biochemical processes in the water column. In February 2020, water samples were collected to characterize the distribution and optical properties of DOM from the Northern Andaman Sea and the Northeastern Bay of Bengal. A high dissolved organic carbon (DOC) concentration appeared in the Northern Andaman Sea, which is strongly affected by the DOM contents of the Irrawaddy and Salween Rivers. A barrier layer that resulted from the freshwater input was observed above the thermocline. This layer was believed to have had a consistent effect on the concentration of DOM in the surface water and contributed to the differences in DOC concentration on each side of the Preparis Channel. Based on the fluorescence excitation emission matrix and parallel factor analysis, four fluorescent components were identified, including three humic-like components (C1, C2, and C4 with their maximal Ex/Em at ≤240/418 nm, 315/384 nm, and 270 (360)/442 nm and represented as peaks A, M, and A+C, respectively) and one protein-like component (C3 with maximal Ex/Em at 275/334 nm and represented as peak T). The humic-like components were mainly derived from terrestrial inputs. Low levels of humic-like components were confined in the upper water, with strong photodegradation in the euphotic zone. C3 was a typical tryptophan-like component that represented freshly produced autochthonous DOM. The correlation between C3 and biological index and apparent oxygen utilization suggested that it was highly bioavailable and not easy to be preserved in the deep sea. Overall, our results showed the distributions of DOM in the Northern Andaman Sea and the Northeastern Bay of Bengal and revealed the behaviors and controlling factors for DOM in the upper water.